2004
DOI: 10.1111/j.1545-5300.2004.04302005.x
|View full text |Cite
|
Sign up to set email alerts
|

Interest in and Barriers to Participation in Multiple Family Groups Among Head and Neck Cancer Survivors and Their Primary Family Caregivers

Abstract: This study examined interest in and barriers to participation in a multiple family group intervention (MFG) for adult cancer survivors and their family caregivers. The intervention was developed to assist families in coping with the persistent challenges of cancer diagnosis, treatment, and rehabilitation. Eighty eligible families having a member diagnosed and treated for cancers of the head and neck region completed a baseline quality of life survey consisting of standardized psychosocial measures, and then al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 34 publications
2
67
0
Order By: Relevance
“…Interventions might be most helpful on a dyadic, rather than an individual basis. Family-focused psychosocial interventions with families managing HNC have received some attention (Ostroff, Ross, Steinglass, Ronis-Tobin, & Singh, 2004), and dyadic coping interventions within the wider chronic illness population indicate promising results (Widmer, Cina, Charvoz, Shantinath, & Bodenmann, 2005). It is currently unknown, however, at what point within the HNC journey such interventions might most helpfully be offered.…”
Section: Discussionmentioning
confidence: 97%
“…Interventions might be most helpful on a dyadic, rather than an individual basis. Family-focused psychosocial interventions with families managing HNC have received some attention (Ostroff, Ross, Steinglass, Ronis-Tobin, & Singh, 2004), and dyadic coping interventions within the wider chronic illness population indicate promising results (Widmer, Cina, Charvoz, Shantinath, & Bodenmann, 2005). It is currently unknown, however, at what point within the HNC journey such interventions might most helpfully be offered.…”
Section: Discussionmentioning
confidence: 97%
“…Its effectiveness is recognised in particular because (Ostroff et al 2004) it reduces family stress, it enhances the sense of competence amongst patients and their families and it increases their adherence to treatments. Multi-family discussion groups are time-limited (four to six sessions); they are especially designed to help family adjustment and coping with illness demands and uncertainty, allowing support from people who are sharing the experience and relieving feelings of isolation (Gonzalez and Steinglass 2002).…”
Section: Conceptualising Psycho-educational Intervention In Cancer Gementioning
confidence: 98%
“…Psycho-educational approaches are shown to be more efficient if developed in multi-family discussion groups (Ostroff et al 2004); this context promotes a nonpathological atmosphere, allowing families to learn and talk about the illness, namely about the way it invaded the family identity and how it interferes in its development. Its effectiveness is recognised in particular because (Ostroff et al 2004) it reduces family stress, it enhances the sense of competence amongst patients and their families and it increases their adherence to treatments.…”
Section: Conceptualising Psycho-educational Intervention In Cancer Gementioning
confidence: 99%
“…This methodological challenge has hampered progress in caregiver research. Indeed, some studies have suggested that identifying a comprehensive yet compact list of barriers to enrollment of family caregivers in familybased research is an important first step in cancer caregiver research [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%